Features of pathological changes in the associative flow of mycoplasmosis - Колич, Н. Б. (Scientific Progress & Innovations, 2016)
Mycoplasmosis pneumonia of pigs is a chronic infectious disease of pigs of all age groups, characterized by exudative-proliferative inflammation of the lungs, intermittent fever, cough and delayed growth and development of piglets, and complications – progressive weight loss. Mycoplasmosis increases the susceptibility of pigs to secondary infections, making it more difficult and often leads to death of animal. We conducted a comprehensive laboratory study of the use of bacteriological, serological and coprologic research methods of pigs 1,5 and 3 months of age. The studies were conducted in the conditions of farms for growing and fattening of pigs in Poltava region. Characteristic of all cases of animals’ death was uneven redness and slight thickening of the skin in the abdomen. The increase and uneven coloration of submandibular, tracheal, inguinal lymph nodes. Lungs with signs of catarrhal pneumonia with lesions predominantly cranial lobes. Some areas of dark red color with a bluish tint, more dense consistency, fall on a common surface, in the lumen of the bronchial – mucous mass. The other part of the body gets mild tuberosity at the age of 1,5 months and more intelligible – at the age of 3 months. In all cases of death of pigs – the pericardium and the pleura with hemorrhage. The spleen is diffusely dark red. The buds are light brown with areas of bluish color. At the age of 1,5 months on the mucosa of a thick intestine there were rounded multiple small formations, protruding into the lumen of the intestine.